Development of Project-Based Information and Communication Technology Vocasional Skills Book for Special Junior High School - Anori, Sari Rahmadina; Huda, Asrul; Anori, Sartika (Jurnal Teknologi Informasi dan Pendidikan, 2024)
ICT vocational skills subject at Special Junior High School did not have a learning book for special need students. As a result, the students who have intellectual disabilities have many problems to learn independently. This condition also impacted on student learning outcomes that did not reach the targeted competencies. The purpose of this research is to produce a project-based ICT vocational skills book for Special Junior High School that is valid, practical and effective for learning uses. This study uses research and development (R&D) method with 4D model through Define, Design, Develop, and Disseminate stages. The data were collected using a questionnaire and one group pre-test and post-test design. The results of the study, it concluded that the project-based ICT vocational skills book for Special Junior High School is feasible, very practical and effective for learning use.